Q. 44.8( 4 Votes )

Resolve each of t

Answer :

= - 2x2 + 7x – 6

Here, coefficient of x2 = -2, coefficient of x = 7and constant term = -6


We shall now split up the coefficient of x i.e., 7 into two parts whose sum is 7 and product is -2 * -6 = 12


Clearly,


4 + 3 = 7 and,


4 * 3 = 12


So, we write middle term 7x as 4x + 3x


Thus, we have


-2x2 + 7x – 6 = -2x2 + 4x + 3x – 6


= -2x (x – 2) + 3 (x – 2)


= (x – 2) (3 – 2x)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Fill in the blankNCERT - Mathematics Exemplar

Resolve each of tRD Sharma - Mathematics

Resolve each of tRD Sharma - Mathematics

Resolve each of tRD Sharma - Mathematics

Resolve each of tRD Sharma - Mathematics